Bariatric Surgery in the Caribbean: Is It Safe in a Low-Volume, Third World Setting?. (8th May 2012) - Dan, Dilip; Singh, Yardesh; Naraynsingh, Vijay; Hariharan, Seetharaman; Maharaj, Ravi; Teelucksingh, Surujpal
Abstract : Bariatric surgery is a well-recognized modality of management of obesity. In addition to obesity, it effectively controls diabetes mellitus, and hypertension. It has been recommended that bariatric surgery should be done in "designated centers" of excellence where there is a high volume of case turnover. Caribbean nations are not spared from the global spread of the obesity epidemic; however, not many patients get the benefits of bariatric surgery. This study aimed to establish that bariatric surgery could be safely and efficiently undertaken in a low-volume center outside the "designated centers" with comparable patient outcomes even in a third world setting. Though "patient numbers" generally imply better outcome, in an environment where these numbers cannot be achieved, patients should not be denied the access to surgery once good outcomes are achieved.